Etiology and types of necrotizing periodontal diseases - Abdullah, Yazeed Abdullah; Albeshr, Abdulhameed G.; Albasher, Ala’a Abdulkalq; Alassiri, Abdullah Saeed; Shater, Mahmood Abdulaziz; Alqahtani, Mohammed Ali; Ageely, Khaled Taib; Alshahrani, Raghad Saeed; Alkhormani, Anas Abed; Bawakid, Alaa Mohammed; Huwaity, Lamia S. A. Al; Albulushi, Rayan Ibrahim (International Journal Of Community Medicine And Public Health, 2021)
Necrotizing periodontal diseases pose a clinical significance because it has been associated with a severe prognosis that can cumulatively lead to rapid tissue destruction. A slow rate of destruction has been reported for patients with necrotizing periodontal diseases, and reports show that chronicity might be a characteristic in some patients, while many patients might also suffer from disease recurrence. The association of other oral lesions might also be a characteristic in some situations, which usually occurs in cases when systemic involvement is present. In the present literature review, we aim to discuss the etiology and types of necrotizing periodontal diseases based on evidence from the different related studies in the literature. Microbiology plays an important role in the pathogenesis of the condition, and some organisms as spirochetes were directly correlated with the etiology of the condition. Evidence also shows that the presence of the different risk factors might be the major contributor to the development of the condition as different risk factors were found to be directly correlated with the disease. Among the different factors, impacted host immune response and the presence of deteriorating systemic conditions have been widely reported in the literature as significant factors predisposing to developing the disease. Other factors as smoking and alcohol consumption, previous history of the disease, and other oral lesions, were also reported. Further research is needed for better classification of the condition and determination of more significant risk factors.